Impact of Job Crafting to Work Engagement: Mediating Role of Person-Job Fit and Job Resources on The Tour Guide - Azizah, Siti Nur; Setyawati, Harini Abrilia (E-Journal of Tourism; Volume 8 Number 2 (September 2021), 2021)
This research was conducted to examine the effect of job crafting to work engagement with person-job fit and job resources ad mediating variables. The population of this study is a tour guide in Jogjakarta, Indonesia with a sample of 125 people in This research was carried out in early January 2020. We used convenience sampling as the sampling technique. A 5-level Likert scale is used to measure respondents’ attitudes. Smart PLS (Partial Least Square) for windows processed the results were obtained with. Research showed that job resources act as a full mediation between the relationship between job crafting and work engagement. And person-job fit variable also has a fully mediating role in the relationship between job crafting and work engagement. The conclusion of this study is that the job resources owned by employees will balance the needs of workers and show a mediating effect so that employees can increase their involvement in work. Likewise, person job fit refers to the relationship between employee characteristics and job characteristics, which is a variable that can increase the job involvement of tour guides. Various practical implications are described in this paper.